Adipositas & Bewegung - Wackerhage H (Deutsche Zeitschrift für Sportmedizin, 2017)
Low birth rates and increased life expectancies have led to population aging e.g. in Japan and Europe. Aging is a time-dependent functional decline that affects most living organisms. The loss of muscle mass and function during normal aging is termed sarcopenia. Sarcopenia is due to many factors including a loss of motor neurons and muscle fibers, type II fiber atrophy anabolic resistance (i.e. less muscle protein synthesis after protein ingestion, resistance exercise and insulin) and impaired muscle regeneration. Sarcopenia is associated with frailty, mortality, problems with performing daily living tasks and falls. The main treatments are safe, effective and attractive resistance training programs with up to 40g of protein in the anabolic window before, during or after resistance exercise and a daily protein intake of at least 1-1.2g per kg body weight (the amount of protein ingestion is more important than potential timing effects). Additional treatments such as creatine or vitamin D might be useful. Finally, drug treatments such as testosterone, -agonists or myostatin inhibitors can potentially be used for some subjects with sarcopenia.KEY WORDS: Sarcopenia, Satellite Cells, Aging, Anabolic Resistance